2011
DOI: 10.1021/nn1035922
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Absorption Backgrounds in Single-Walled Carbon Nanotube Spectra

Abstract: The sources of broad backgrounds in visible-near-IR absorption spectra of single-walled carbon nanotube (SWCNT) dispersions are studied through a series of controlled experiments. Chemical functionalization of nanotube sidewalls generates background absorption while broadening and red-shifting the resonant transitions. Extensive ultrasonic agitation induces a similar background component that may reflect unintended chemical changes to the SWCNTs. No major differences are found between spectral backgrounds in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
172
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(188 citation statements)
references
References 43 publications
(87 reference statements)
12
172
3
1
Order By: Relevance
“…The fitting function consisted of a sum of six Lorentzian peaks, one for each armchair (10,10) through (5,5), along with a polynomial function used to fit the absorption baseline/background. While the absorption background has multiple possible intrinsic and extrinsic origins, 11,12 it is evident that the fit produces excellent agreement with the experimental data (adjusted R 2 goodness-of-fit value = 0.996). Similar Lorentizian fits for the absorption spectra of samples #1, 3, 4, 5 and 6 result in adjusted R 2 goodness-of-fit values = 0.984, 0.998, 0.997, 0.998 and 0.998, respectively (see supplementary Fig.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The fitting function consisted of a sum of six Lorentzian peaks, one for each armchair (10,10) through (5,5), along with a polynomial function used to fit the absorption baseline/background. While the absorption background has multiple possible intrinsic and extrinsic origins, 11,12 it is evident that the fit produces excellent agreement with the experimental data (adjusted R 2 goodness-of-fit value = 0.996). Similar Lorentizian fits for the absorption spectra of samples #1, 3, 4, 5 and 6 result in adjusted R 2 goodness-of-fit values = 0.984, 0.998, 0.997, 0.998 and 0.998, respectively (see supplementary Fig.…”
Section: Introductionmentioning
confidence: 77%
“…Armchairenriched samples #3 and #4, which are produced from HiPco material, absorb mainly in the green region, producing suspensions that are colored magenta to purple, depending on the varying amounts of (7,7), (8,8), and (9,9) absorbed. Finally, armchair-enriched arc-discharge material (sample #6) appears green in color due to dual absorption in both the red, due to the first optical transitions of (10,10) and (11,11), and in the blue, due to the second optical transitions of (11,11) and (12,12). Hence, all observed colors for these suspensions obey the rules of subtractive color theory and are a result of the highly spectrally-concentrated absorption bands of armchair SWCNTs, a direct and macroscopic consequence of their excitonic optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are another two absorption peaks for (9, 1) and (7, 5) SWCNTs, which can be seen at 915 nm and 1026 nm, respectively [28,30]. As a result, the aggregation of specific spectra features led to the broadening of the absorption peaks [30][31].…”
Section: Resultsmentioning
confidence: 98%
“…For a given absorption spectrum of SWCNTs, it has been shown that well-resolved features mean the fraction of individual SWCNTs is higher [29]. The I MAX -to-FWHM ratio has been proven to be related to the degree of SWCNT debundling and aggregation, which is used to evaluate the purity of SWCNT samples [31][32]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is illustrated in Figure 7a, which depicts 30% cmc (right vial) and 300% cmc (left vial) solution left standing for 14 days after ultrasonication for 60 minutes at 200 W. Whereas a uniform dispersion was maintained in the 300% cmc surfactant solution, significant sedimentation was observed at 30% cmc, indicating the critical role of the surfactant concentration. UV-Vis absorption spectroscopy may be used to characterize the quality of the CNT dispersion 29 and typically via the analysis of the resonance peak ratio 30 . This is depicted in Figure 7b for the two different surfactant concentrations treated at 200 W.…”
Section: Resultsmentioning
confidence: 99%